Thrombo-embolic events in left ventricular endocardial pacing: long-term outcomes from a multicentre UK registry. Issue 12 (1st June 2018) - Sawhney, Vinit; Domenichini, Giulia; Gamble, James; Furniss, Guy; Panagopoulos, Dimitrios; Lambiase, Pier; Rajappan, Kim; Chow, Anthony; Lowe, Martin; Sporton, Simon; Earley, Mark J; Dhinoja, Mehul; et al.
Abstract: Aims: Endocardial left ventricular (LV) pacing is a viable alternative in patients with failed coronary sinus (CS) lead implantation. However, long-term thrombo-embolic risk remains unknown. Much of the data have come from a small number of centres. We examined the safety and efficacy of endocardial LV pacing to determine the long-term thrombo-embolic risk. Methods and results: Registries from four UK centres were combined to include 68 patients with endocardial leads with a mean follow-up of 20 months. These were compared to a matched 1:2 control group with conventional CS leads. Medical records were reviewed, and patients contacted for follow-up. Ischaemic stroke occurred in four patients (6%) in the endocardial arm providing an annual event rate (AER) of 3.6% over a 20 month follow-up; compared to 9 patients (6.6%) amongst controls with an AER of 3.4% over a 23-month follow-up. Regression analyses showed a significant association between sub-therapeutic international normalized ratio and stroke ( P  = 0.0001) in the endocardial arm. There was no association between lead material and mode of delivery (transatrial/transventricular) and stroke. Mortality rate was 12 and 15 per 100 patient years in the endocardial and control arm respectively with end-stage heart failure being the commonest cause. Conclusion: Endocardial LV lead in heart failure patients has a good success rate at 1.6 year follow-up. However, it is associated with a thrombo-embolic risk (which is not different from conventional CS leads) attributable to sub-therapeutic anticoagulation. Randomized control trials and studies on non-vitamin K antagonist oral anticoagulants are required to ascertain the potential of widespread clinical application of this therapeutic modality.